DNA stretching induces Cas9 off-target binding and cleavage - Newton,M; Taylor,B; Driessen,R; Roos,L; Cvetesic,N; Allyjaun,S; Lenhard,B; Cuomo,ME; Rueda,D (Nature Structural and Molecular Biology, 2018)
CRISPR/Cas9 is a powerful genome editing tool, but spurious off-target edits present a barrier towards therapeutic applications. To understand how CRISPR/Cas9 discrimi-nates between on- and off-targets, we have developed a single-molecule assay com-bining optical tweezers with fluorescence to monitor binding to λ-DNA. At low forces, the Streptococcus pyogenes Cas9 complex binds and cleaves DNA specifically. At higher forces, numerous off-target binding events appear repeatedly at the same off-target sites in a guide-RNA-sequence dependent manner, driven by the mechanical distortion of the DNA. Using single-molecule FRET and cleavage assays, we show that DNA bubbles induce off-target binding and cleavage at these sites, even with 10 mis-matches, as well as at previously identified in vivo off-targets. We propose that duplex DNA destabilization during cellular processes (e.g., transcription, replication, etc) can expose these cryptic off-target sites to Cas9 activity, highlighting the need for improved off-target prediction algorithms.